An Evaluation of Agricultural Communications Faculty Members’ Mentoring Experiences - Taylor K Ruth; Ricky W Telg; Lisa K Lundy (Journal of Applied Communications, 2020)
Agricultural communications programs are expected to grow and emerge over the next decade. For these programs to find success, faculty leading them will need to be properly supported through effective mentoring. The purpose of this study was to evaluate the current mentoring of agricultural communications faculty across the country. In November 2019, an online survey instrument was distributed to a census of members of the Society of Agricultural Communications Scholars listserv. Survey respondents reported mentoring was not formally required, and most of the respondents received informal mentoring. Mentors were most frequently non-agricultural communications faculty in the respondents’ respective department or an agricultural communications faculty at another institution. Mentees met with mentors as needed and typically discussed teaching, research, or administrative questions. However, the mentees perceived navigating promotion and tenure, work-life balance, and research as the most important topics for their success. Similar to past research, time was the biggest barrier to effective mentoring relationships. The findings from this study provide a baseline to understand what mentoring looks like for agricultural communications faculty and can help administrators provide proper support for effective faculty mentor programs.
Keywords: Mentorship; Mentoring; Faculty; Evaluation